(untitled) (Contemporary Journal of Social Science Review, 2025)
This qualitative study explored the intersection of Islamic theology and inclusive education in Punjab, Pakistan, with the aim of understanding how religious interpretations, institutional factors, and policy implementation influence educational inclusion for children with disabilities. Using a case study approach, semi-structured interviews were conducted with parents, educators, school heads, School Management Committee (SMC) chairpersons, and District Education Officers (DEOs). Data were analyzed thematically to address three research questions: (1) the influence of Islamic theology on attitudes toward children with disabilities, (2) institutional barriers to inclusive education, and (3) alignment between inclusive education policies and local cultural-religious contexts. Findings revealed that authentic Islamic principles emphasizing compassion, equality, and human dignity often encouraged inclusive attitudes, yet cultural misinterpretations particularly in rural areas reinforced stigma. The study identified several institutional challenges. These included lack of teacher training programs, inaccessible infrastructure, rigid curriculum, and shortages of assistive devices. Rural schools faced these problems more severely than urban ones. Although provincial policies aligned with international frameworks like the UNCRPD and the Salamanca Statement, a significant gap remained between policy and practice. This gap was mainly due to weak monitoring, limited resources, and poor adaptation to local cultural contexts. The study concludes that achieving effective inclusion requires a combined effort. This includes engaging with theological perspectives, strengthening institutions, and designing policies that are culturally sensitive. The findings offer important insights for policymakers, educators, and community leaders. Practical recommendations are also provided to help bridge the divide between the ideals of inclusion and what happens in reality within schools.